A smoking gun evidence on the dynamics of the continuum electron-positron-proton three-body system - Barrachina Tejada, Raul Oscar (2012)
Researchers from the Bariloche Atomic Centre in Argentina have recently proposed to study the ionization of an atom by the impact of a positron, not by the standard approach of analysing the velocity spectra of the emitting electron and/or the scattered projectile, but by looking at the proton left behind. The receding ion, playing the role of a smoking gun, is shown to give detailed information on the electron and the positron after the collision.